EKSPLORASI KEUNGGULAN METODE DAKWAH TEMATIK DALAM TAFSIR AL-QUR’AN - Nadjamuddin Shiddiq, Ahmad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Thematic methods of da'wah in Qur'anic interpretation have become a significant approach in enhancing the understanding and delivery of Islamic teachings more effectively and relevantly in the context of modern times. This article aims to explore the advantages of thematic da'wah methods in Qur'anic interpretation, focusing on a critical analysis of their contributions to Islamic teaching and preaching. Through the thematic approach, Qur'anic verses related to a specific topic are collected and comprehensively analyzed, resulting in a more holistic and thorough understanding. This study identifies several key advantages of the thematic da'wah method, including the ability to systematically link verses, enhance the relevance of da'wah messages in contemporary contexts, and facilitate deeper understanding of specific themes in the Qur'an. Moreover, this method allows interpreters to integrate various scientific disciplines in their interpretation, producing a richer and more multidimensional exegesis. Thus, the thematic da'wah method in Qur'anic interpretation not only enriches the exegesis literature but also makes a significant contribution to improving the effectiveness of Islamic preaching. Keywords: thematic approach, Qur'anic interpretation, effective da'wah